1999
DOI: 10.1042/bj3450017
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of c-Src by prolactin is independent of Jak2

Abstract: Interaction of prolactin (PRL) with its receptor (PRLR) leads to activation of Jak and Src family tyrosine kinases. The PRL/growth hormone/cytokine receptor family conserves a proline-rich sequence in the cytoplasmic juxtamembrane region (Box 1) required for association and subsequent activation of Jaks. In the present work, we studied the mechanisms underlying c-Src kinase activation by PRL and the role that Jak2 plays in this process. PRL addition to chicken embryo fibroblasts (CEF) expressing the rat PRLR l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 14 publications
(23 reference statements)
1
24
1
Order By: Relevance
“…Although several groups have implicated the MAP and PI3 kinases as downstream effectors of crosstalk between PR and c-Src (Lange 2004), our present results indicate that these pathways do not participate in the synergistic effect of PC PRL on the MMTV-LTR. It is also well established that Jak2 (Campbell et al 1994, Rui et al 1994 and Src family kinases (Clevenger & Medaglia 1994, Al-Sakkaf et al 1997, Fresno Vara et al 2000 can converge during PRL signaling, where the Src family kinase p59 (Fyn) can preform with all PRLR isoforms (Clevenger & Medaglia 1994). While a role for STAT1 or STAT3 in the synergistic response by the MMTV-LTR to PCPRL cannot be ruled out, our data do indicate that STAT5a and STAT5b are not required.…”
Section: Discussioncontrasting
confidence: 38%
“…Although several groups have implicated the MAP and PI3 kinases as downstream effectors of crosstalk between PR and c-Src (Lange 2004), our present results indicate that these pathways do not participate in the synergistic effect of PC PRL on the MMTV-LTR. It is also well established that Jak2 (Campbell et al 1994, Rui et al 1994 and Src family kinases (Clevenger & Medaglia 1994, Al-Sakkaf et al 1997, Fresno Vara et al 2000 can converge during PRL signaling, where the Src family kinase p59 (Fyn) can preform with all PRLR isoforms (Clevenger & Medaglia 1994). While a role for STAT1 or STAT3 in the synergistic response by the MMTV-LTR to PCPRL cannot be ruled out, our data do indicate that STAT5a and STAT5b are not required.…”
Section: Discussioncontrasting
confidence: 38%
“…It is plausible that a second, Src-dependent pathway might be responsible for downregulation of PRLr in Ser349 phosphorylation-and ubiquitination-independent manner. In this regard, it is worth noting that c-Src can be activated by PRL independent of Jak2 in chicken embryo fibroblasts (Fresno Vara et al 2000). These pathways might either synergize to facilitate optimal/efficient PRLr downregulation or might differentially contribute to PRLr endocytosis and degradation in a cell-type-specific manner.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling through the PRLR has been shown to phosphorylate Akt1 via Src-mediated signal transduction to PI3 kinase but not through a Stat5-dependent mechanism in lymphoid and breast cancer cells (for references, refer to Clevenger et al [13]). Since our recent study and that of Fresno Vara et al (19) suggested that the functional ablation of Jak2 did not abolish the PRLR-induced activation of Src, it was surprising to note that Akt1 expression and activation was significantly reduced in Jak2 conditional knockout cells (42). We therefore reasoned that mammary epithelial cells might possess alternative mechanisms to regulate the expression of Akt1 in a Jak2/Stat5-dependent manner.…”
mentioning
confidence: 95%